Kesalahan Umum Pelafalan Makharijul Huruf pada Pembaca Al-Qur'an dan Solusinya - Randy Putra Alamsyah; Mardiah Abbas; Rizky Puji Gunawan Nasution; M. Fajri Nasution; Ilham Hasan; M. Fathi Aswan; Reza Firmansyah; M. Rizky Harahap (Journal of Innovative and Creativity, 2025)
Proper pronunciation of the hijaiyah letters is an important aspect of reading the Qur'an. Mispronunciation of the letters (makhārijul ḥurūf) is common among Qur'an readers, both beginners and experienced, and can affect the quality of their reading. This study aims to identify the types of mispronunciation, understand the causal factors, and formulate effective remedial strategies for learning the Qur'an. This study used a descriptive qualitative approach with library research. Data were obtained from literature in the form of tajwid textbooks, scientific articles, and relevant previous research. Data analysis techniques were carried out through systematic data reduction, presentation, and drawing conclusions. Source triangulation was used to ensure the validity of the information and strengthen the findings. The results of the study show that errors in pronunciation of makharijul huruf most often occur in the letters halkiyyah, oraliyyah, syafawiyyah, and mad letters, with errors in the form of mixed sounds, inaccurate stress, and unclear articulation. Causative factors include limited understanding of practical recitation, lack of teacher guidance, learning methods that do not emphasize phonetic exercises, incorrect reading habits, and the influence of the mother tongue or regional dialect. Recommended improvement strategies include talaqqi and musyafahah methods, focused letter practice, use of audio-visual media, and regular reading evaluations. It is hoped that this study can become a reference for Al-Qur'an educators and readers to improve the quality of reading according to tajwid rules.